Designing AI-Driven Chatbots for Adolescent Mental Health Support in Rural Schools - Kasse, Yubina; Riantofani, Riantofani; Kiftiyah , Kiftiyah; Rahmi, Rahmi (International Journal of Research in Counseling, 2025)
Mental health among adolescents in rural schools is increasingly recognized as a critical public health issue, yet these areas often lack access to professional psychological support. This study aims to explore the design considerations and implementation strategies of AI-driven chatbots as accessible and scalable tools for supporting adolescent mental health in rural educational settings. Using a qualitative research design, the study reviews existing literature and analyzes user-centered design principles, AI natural language processing capabilities, and ethical constraints in deploying mental health chatbots. Findings suggest that culturally-sensitive content, confidentiality safeguards, and integration with school counseling protocols are crucial to the effectiveness of such tools. The study proposes a conceptual design framework for future development and implementation. This research contributes to the development of inclusive and adaptive digital interventions in underserved communities.